Perceived quality of care and choice of healthcare provider in informal settlements - Chris Conlan; Teddy Cunningham; Sam Watson; Jason Madan; Alexandros Sfyridis; Jo Sartori; Hakan Ferhatosmanoglu; Richard Lilford (Public Library of Science (PLoS), 2023)
When a person chooses a healthcare provider, they are trading off cost, convenience, and a latent third factor: "perceived quality". In urban areas of lower- and middle-income countries (LMICs), including slums, individuals have a wide range of choice in healthcare provider, and we hypothesised that people do not choose the nearest and cheapest provider. This would mean that people are willing to incur additional cost to visit a provider they would perceive to be offering better healthcare. In this article, we aim to develop a method towards quantifying this notion of "perceived quality" by using a generalised access cost calculation to combine monetary and time costs relating to a visit, and then using this calculated access cost to observe facilities that have been bypassed. The data to support this analysis comes from detailed survey data in four slums, where residents were questioned on their interactions with healthcare services, and providers were surveyed by our team. We find that people tend to bypass more informal local services to access more formal providers, especially public hospitals. This implies that public hospitals, which tend to incur higher access costs, have the highest perceived quality (i.e., people are more willing to trade cost and convenience to visit these services). Our findings therefore provide evidence that can support the 'crowding out' hypothesis first suggested in a 2016 Lancet Series on healthcare provision in LMICs.